A Basic Elements and Characteristics in Building an Expert System - Hasanuddin Sirait (Journal Neosantara Hybrid Learning, 2023)
The basic elements and characteristics of an expert system are important in the application of an expert system, so that in the application of a makar expert system, the basic elements and characteristics of an expert system are first known. By knowing the basic elements and characteristics of an expert system, the goals and benefits of making an expert system can be more focused and have good fundamentals.This journal is a learning system in designing and knowing expert systems that have fundamental characteristics, so that the utilization that is carried out can run well.